Role of Professional Organizations in Promoting Your Biomedical/Clinical Engineering Career - Subhan, Arif; Painter, Frank; Greenwood, Kim (CMBES Proceedings, 2023)
A Biomedical/Clinical Engineering professional, whether they are a biomedical technician or a biomedical/clinical engineer needs to know what factors help grow and enhance their career. Of course education, experience, trainings and certifications matter, but often many fail to recognize the important role professional organizations (e.g. AAMI, CMBES, ACCE and others) play in providing that extra push, guidance and experience that sets them apart as they move ahead in their career. Joining a professional organization at any level and any time during their career can help the Biomedical/Clinical Engineering professional boost their career. This presentation will draw upon decades of the experience the presenters had with the professional organizations and how it helped enhance their Biomedical /Clinical Engineering career.